FAKTOR-FAKTOR YANG MEMPENGARUHI PENGAMBILAN KEPUTUSAN PETERNAK DALAM MELAKUKAN PROGRAM VAKSINASI JEMBRANA PADA SAPI BALI - Widia Kamalasari; Fikri Ardhani; Firda Juita (Universitas Mulawarman, 2019)
ABSTRACT Jembrana vaccination program in Bali cattle has been done since 2006. The decision of farmers in the adoption of Jembrana vaccination technology in Bali cattle can be influenced by many factors. This study aims to determine the internal and external factors affect the decision of farmers in conducting Jembrana vaccination program in Bali cattle. The data taken include primary data and secondary data. The method of determining the location in the study was taken by purposive. Proportional sampling method and simple random sampling. The measurement used in this research in Likert scale. Analyzed by qualitative descriptive method. This study show that internal factors consisting enough influence to decision of farmer in conducting Jembrana vaccination program on Bali cattle with an average score of 46.20. External factors consisting enough to affect the decision of farmers in conducting Jembrana vaccination program in Bali cattle with an average number of scores 18.07.